Mental Health Students' Profiling Across Urban and Rural Areas - Pramesti, Getut; Umiyati, Tien; Permata, Seta Galih; Listiyanto, Fajar (Personifikasi: Jurnal Ilmu Psikologi, 2025)
Mental health is a condition in which individuals can realize their potential, cope with life's pressures, work productively, and make contributions. Therefore, mental health is very important for humans, especially for students. A mental health profile is one of the efforts in identifying factors that affect students' mental health. This study is a quantitative descriptive, inferential study. In the inferential, 3-way MANOVA analysis is used, and the description is equipped with correspondence visualization. The population in this study was high school students in urban and rural areas in Surakarta, Central Java, Indonesia, totalling 1240 students. The sampling used was cluster random, totaling 134 students. 2 suburban and 2 sub-rural areas were taken to compare their mental health. In addition to demographics, other research variables were also selected in the form of gender, student guardians, number of social media applications, age, distance, and student weight. From the discussion, the results indicate that there is a joint influence between gender, number of social media applications, and demographics on students' mental health. The existence of interaction of influence indicates that synergy between schools and related governments is needed to make the best policies to anticipate the high level of mental health problems of students in urban and rural areas. In contrast, students with low health problems were identified as students whose homes were close to school, users of 1 social media application, and students with ideal body weight.